2015
DOI: 10.1371/journal.pone.0128851
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Parasite Prevalence Corresponds to Host Life History in a Diverse Assemblage of Afrotropical Birds and Haemosporidian Parasites

Abstract: There is an error in the fifth sentence of the first paragraph of the Results section. The correct sentence is: Pigeons and doves (Columbidae) sampled in this study were primarily parasitized by Haemoproteus parasites in the subgenus Haemoproteus (unpublished molecular analyses). However, one individual (African olive pigeon) was parasitized by a novel Haemoproteus lineage that was most closely related to the strigiform parasite Haemoproteus syrnii (subgenus Parahaemoproteus).There is an error in the second se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…To control for any taxonomic dependency in the data, we first tested the significance of three nested random effects, i.e., family, genus nested in family, and species nested in genus nested in family. This approach allows accounting for statistical non-independence in the data owing to shared life history and identifying the taxonomic level at which these unexplained effects might occur (Lutz et al 2015;Bridge et al 2016). As both seed bank type and density are known to vary considerably across habitat types (Fenner and Thompson 2005), we also included species nested in habitat as a potential random factor.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…To control for any taxonomic dependency in the data, we first tested the significance of three nested random effects, i.e., family, genus nested in family, and species nested in genus nested in family. This approach allows accounting for statistical non-independence in the data owing to shared life history and identifying the taxonomic level at which these unexplained effects might occur (Lutz et al 2015;Bridge et al 2016). As both seed bank type and density are known to vary considerably across habitat types (Fenner and Thompson 2005), we also included species nested in habitat as a potential random factor.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The functions lmer and glmer in the R package lme4 (Version 1. 1-13;Bates et al 2015) were used to fit LMMs and GLMMs while the lmerTest package was used to test for the significance of fixed and random effects (Kuznetsova et al 2016).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Recent studies have shown in regions with high avian diversity and in specific host populations [48], the Leucocytozoon diversity would be high[49] accessibility of a screening method that can amplify all three genera can serve up in understanding the accurate diversity and ecology of all three genera of avian haemosporidian parasites. Since now, the only screening process that could distinguish all three genera in a single method were microscopy and the restriction digestion protocol of Beadell & Fleischer [50], but both take drastically more time than the real-time PCR and nested PCR protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Such differences among the bird taxa are difficult to explain. In some cases, they can correlate with different capacities of the host immunity to defend itself against specific parasite infections [ 10 , 11 ] or with the ecology, habitat preferences and behaviour of the hosts [ 12 14 ]. According to studies on different corvid species, such as crows, magpies and jays, the avian family of Corvidae seems to harbour a great amount of haemosporidian parasites [ 15 18 ].…”
Section: Introductionmentioning
confidence: 99%